Proceedings of the 2021 CHI Conference on Human Factors in Computing Systems 2021
DOI: 10.1145/3411764.3445665
|View full text |Cite
|
Sign up to set email alerts
|

Sharing Heartbeats: Motivations of Citizen Scientists in Times of Crises

Abstract: With the rise of COVID-19 cases globally, many countries released digital tools to mitigate the efects of the pandemic. In Germany the Robert Koch Institute (RKI) published the Corona-Data-Donation-App, a virtual citizen science (VCS) project, to establish an early warning system for the prediction of potential COVID-19 hotspots using data from wearable devices. While work on motivation for VCS projects in HCI often presents egoistic motives as prevailing, there is little research on such motives in crises sit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Many online citizen science projects, such as eBird and iNaturalist, thrived in the pandemic, with increases in observations made by the public as they sought relief in nature, although this varied according to location, with community science participants shifting to more urban settings (Crimmins et al, 2021;Rose et al, 2020). One project found that the motivations for joining changed during the pandemic, from more extrinsic to more intrinsic drivers (Diethei et al, 2021). Digital technologies aided this success, as they linked socially distanced professional scientists with citizen scientists.…”
Section: The Impact Of the Covid-19 Pandemic On Citizen Science Projectsmentioning
confidence: 99%
“…Many online citizen science projects, such as eBird and iNaturalist, thrived in the pandemic, with increases in observations made by the public as they sought relief in nature, although this varied according to location, with community science participants shifting to more urban settings (Crimmins et al, 2021;Rose et al, 2020). One project found that the motivations for joining changed during the pandemic, from more extrinsic to more intrinsic drivers (Diethei et al, 2021). Digital technologies aided this success, as they linked socially distanced professional scientists with citizen scientists.…”
Section: The Impact Of the Covid-19 Pandemic On Citizen Science Projectsmentioning
confidence: 99%
“…MaxQDA has been used in various other research projects in HCI (e.g. [23,48,104]) and allows researchers to code and analyze freeform text such as interview transcripts or, in our case, open feedback that users provided at the end of the experiment. Codes (i.e., category labels) were derived by highlighting important phrases in the participants' answers and summarizing their semantic content in a short descriptive text.…”
Section: Qualitative Data (Rq6 and Rq7)mentioning
confidence: 99%
“…It has been approached primarily in the healthcare domain [27]. Recent applications include the Corona-Data-Donation-App by the Robert Koch Institute in Germany, where donors could share data from fitness trackers and smartwatches to understand better the spread of COVID-19 [20,46]. And the COVID-RED project from the Julius Center in The Netherlands, collecting data from wearable devices with a similar approach and objectives [35].…”
Section: Data Donationmentioning
confidence: 99%